Genetic Diversity Analysis by SSR Markers in Melia dubia Cav. -A Fast Growing Multipurpose Tree Species - Loushambam, R. S.; Devakumar, A. S. (International Journal of Bio-resource and Stress Management, 2023)
The present work was conducted in the year 2019 at the department of Forestry and Environmental Science, GKVK, University of Agricultural Sciences, Bengaluru Karnataka, India aimed to estimate the genetic variation among the populations of Melia dubia. 12 SSR primers producing polymorphic and monomorphic bands were analysed. The fresh and matured leaf sample was collected from the South India germplasm bank of Melia dubia established and maintained by Karnataka Forest Department (KFD) in collaboration with Institute of Forest Genetics and Tree Breeding (IFGTB), Coimbatore at Hoskote near Bengaluru, is a part of rural Bengaluru district, Karnataka, India. Leaf surface was cleaned by wiping with alcohol and carried to the laboratory in the ice bucket. Samples were preserved at -86˚C in a deep freezer. Genetic distances were calculated for all the accession lines studied by SSR PCR. The polymorphic information content (PIC) varied from 0.18–0.35, with an overall mean of 0.28. Nei’s gene diversity (H) ranged from 0.22–0.45, with an overall mean of 0.34. Alleles maker-1 ranged between 1 and 4, with an average of 2.7 alleles marker-1. Genetic distances were used to generate a dendrogram . An UPGMA dendrogram based on similarity coefficient indices revealed high genetic diversity and segregate into thirteen distinct clusters. This can be attributed to highly cross-pollinating nature of the species. and small distributional range in the area. Based on the genetic variability found, tree improvement strategies could be developed for conservation and further improvement of the species.